A Financial and Banking Perspective on the Significance of Cybersecurity in Fiscal and Monetary Policies in the Digital Age - Mohammed Madlool Ali Al-Sultan; Nooraldeen sabah mahdi kmalaldeen; Hayder Mohammed Kareem Al shebly (Peerian Journals Publishing, 2025)
The research focused on the concept of cyber security, its importance in financial and monetary institutions, the most prominent tools followed by cyber security, the challenges and digital attacks that these institutions are exposed to by hackers and financial fraud criminals via the Internet. It also focused on the most important applications and solutions followed by cyber security in these institutions as economic, financial and monetary policies to prevent digital fraud. The digital challenges and attacks that financial and banking institutions are exposed to, whether through financial fraud, malware, threats, hacking, etc., require adopting appropriate solutions and enhancing cyber security tools and applications, which refer to the security of the network, programs, applications, information, and infrastructure, in addition to flexibility, governance, and cyber security awareness, as well as raising awareness among employees and customers of financial and banking institutions, adopting multi-factor authentication, biometric data, automatic logout, strong firewalls, etc.
Keywords: cyber security; cyber security challenges